Concept of Aam in Ayurveda and its Importance in Treating Diseases - Anand, Kumar; Dimple; Baishya, Koushik (International Research Journal of Ayurveda & Yoga, 2022)
Aam is the Apakva Ahara Rasa formed due to the action of Mandagni on ingested food. It is the root cause of many diseases. Due to its distinct qualities it can obstruct the Srotas. Hence the Doshas start accumulating at the site of obstruction and cause diseases. Depending upon its association, diseases can be divided into two groups - Sama and Nirama. In Ayurveda various Acharyas have described about qualities, features and treatment modalities of Aam. It is very important to distinguish between Sama and Nirama Avastha of the body before treating any disease. Because, in the presence of Aam and its causative factor Mandagni, it is not possible to digest Dosha, Ahara and even Ousadh. This leads to formation of more Aam and further increases the severity of the disease. Therefore in Sama diseases, Aam pacifying treatment, such as Apatarpan, has to be applied first and only after attaining Nirama Avastha, other disease specific treatment should be applied.